Long-term exposure to monoclonal anti-TNF is associated with an increased risk of lymphoma in BAFF-transgenic mice. (30th May 2021) - Nocturne, Gaetane; Ly, Bineta; Paoletti, Audrey; Pascaud, Juliette; Seror, Raphaele; Nicco, Carole; Mackay, Fabienne; Vincent, F B; Lazure, Thierry; Ferlicot, Sophie; Stimmer, Lev; Pascal, Quentin; et al.
Summary: The impact of treatment on the risk of lymphoma in patients with rheumatoid arthritis (RA) is unclear. Here, we aimed to assess if the risk of lymphoma differs according to the type of tumor necrosis factor inhibitor (TNFi), comparing monoclonal anti-TNF antibodies to the soluble TNF receptor. We used B cell activating factor belonging to the TNF family (BAFF)-transgenic (Tg) mice as a model of autoimmunity-associated lymphoma. Six-month-old BAFF-Tg mice were treated with TNFi for 12 months. Histological examination of the spleen, assessment of the cellular composition of the spleen by flow cytometry and assessment of B cell clonality were performed at euthanasia. Crude mortality and incidence of lymphoma were significantly higher in mice treated with monoclonal anti-TNF antibodies compared to both controls and mice treated with the soluble TNF receptor, even at a high dose. Flow cytometry analysis revealed decreased splenic macrophage infiltration in mice treated with monoclonal anti-TNF antibodies. Overall, this study demonstrates, for the first time, that a very prolonged treatment with monoclonal anti-TNF antibodies increase the risk of lymphoma in B cell-driven autoimmunity. These data suggest a closer monitoring for lymphoma development in patients suffering from B cell-driven autoimmune disease with long-term exposure to monoclonal anti-TNF antibodies. Graphical Abstract: